22q11.2 Deletion Syndrome: Symptoms, Diagnosis, Treatment - Leyla S. Namazova-Baranova; Olga V. Ginter; Tatyana A. Polunina; Irina V. Davydova; Kirill V. Savostyanov; Alexandr A. Pushkov; Natalya V. Jourkova; Tatyana Y. Mospan (Вопросы современной педиатрии, 2016)
The article analyzes the consequences of chromosomal abnormalities caused by the deletion of a small piece of chromosome 22. This syndrome results in diverse clinical manifestations: congenital heart defects, abnormalities in the large vessels, congenital defects in the maxillofacial area, as well as the endocrine and immune disorders. 22q11.2 deletion syndrome — del 22q11.2 (22q11DS) may have more than 180 different physical, functional and mental associations that affect the patient’s health and quality of life since very birth. Clinical diagnosis and early diagnostics are essential to optimize treatment, and awareness and understanding of the pathological processes in del 22q11.2 definitely involve the use of the multidisciplinary treatment principles. The article describes the modern scientific understanding of 22q11.2 deletion syndrome based on the experience of foreign and Russian authors. The basic clinical symptoms, diagnosis and recommendations for screening and treatment of this kind of patients are described.